Gamers with Different Ability and the role of EAI (E-Sports Ability Indonesia) - Charlie Tjokrodinata; Cendera Rizky Anugrah Bangun; Fakhriy Dinansyah; Artika Rachmi Farmita (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2022)
This research project is intended to explore the way people with disability in accessing mobile gaming especially in E-Sports. Games are framed as sources of cultural capital and sites of pleasure and entertainment. Unfortunately, people with disabilities are often materially and culturally excluded from both systems through inaccessible interfaces, and also a lack of representation in games’ content.  Mass Media likewise plays a crucial role in shaping public perception and influencing the powers that be, however the representation is still lacking and requires communities like  E-Sports Ability Indonesia (EAI) to help amplify the message. EAI is a community that was formed based on the awareness that gamers with physical limitations have the same rights as other gamers, it’s to enjoy the game and participate in various e-Sport championships. EAI is active in advocating people with disabilities to participate in activities related to e-Sport. Methodology used in this article is post-positivist approach with interview and FGD methods, both from EAI (E-Sport Ability Indonesia), gamers, and PB E-Sport Indonesia. This article is expected to give further insight about the role of communities like EAI in providing better access to  people with disabilities in playing video games and participating in E-Sport events.